PENGARUH KEPUASAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT GLOBAL WELINDO BATAM - -, Alfin; Simanjuntak, Jontro (SCIENTIA JOURNAL, 2022)
An organization can be said to go forward or backward depending on its human resources. A way is needed so employees can improve their performance well in carrying out company activities. So that can increase employee performance, it is necessary to pay attention to job satisfaction and work motivation of employees. This study aims to determine the effect of job satisfaction and work motivation on employee performance at PT Global Welindo Batam. This study uses quantitative methods with the nature of development research. This study has a population of 110 people. And the sampling technique used in this research uses non-probability sampling with saturated sampling technique, where the total population is the same as the number of samples. The results of this research indicate that job satisfaction and work motivation simultaneously affect employee performance at PT Global Welindo Batam with a determination coefficient of 62.9%.